External Factors Influencing the Cognitive Response of Impulse Buying Behaviour amongst Generation Y Students - Neves, Jacinta Ana; Redda, Ephrem Habtemichael; de Klerk, Natasha; de Klerk, Natasha (Journal of Economics and Behavioral Studies, 2018)
Impulse buying behaviour has been recognised as a key research concern amongst academic researches and marketers. At one time or another a large amount of consumers purchases on impulse. Evidence from the literature indicates that external factors, such as in-store atmosphere, in-store browsing, in-store layout, salespersons, promotions and reference groups are important antecedents of impulse purchases. The cognitive response to act on impulse purchase is triggered by external factors to buy on impulse. This paper reports on a study undertaken to determine the external factors influencing the cognitive response of impulse buying behaviour amongst Generation Y students. Generation Y are labelled as individuals born between 1986 and 2005. The study employed a quantitative method, whereby a structured, self-administered questionnaire was used to collect data from a non-probability convenience sample of 349 students (aged 18 to 24 years), across two South African public higher education institutions’ campuses located in the Gauteng province. The collected data was examined using descriptive statistics, confirmatory factor analysis, reliability, correlation analysis and regression analysis. The coefficient of multiple determination (R2) was 0.070 that implies that in-store atmosphere, in-store browsing and promotions can predict seven percent of the variance in Generation Y students’ cognitive response to buy on impulse, which proposes that other variables influence Generation Y students’ cognitive response to buy on impulse.